Analyzing the Effects of Financial Indicators on Stock Prices in Non-Cyclical Consumer Firms: Evidence from Indonesia - Siagian, Novianti; Winingrum W.A. , Sri Putri (Indonesian Financial Review, 2025)
This study examines the effect of short-term debt, financial leverage, and market value on stock prices of non-cyclical consumer companies listed on the Indonesia Stock Exchange during the 2021–2025 period. Using a quantitative explanatory approach, the analysis applies panel data regression estimated with EViews. The results show that short-term debt and financial leverage do not have a statistically significant impact on stock prices, indicating that liquidity and capital structure are not primary valuation considerations in this defensive sector. In contrast, market value, proxied by earnings per share (EPS), has a positive and significant effect on stock prices, highlighting the central role of profitability and investor perception in price formation. These findings suggest that the relevance of financial indicators is sector-dependent, with profitability-based signals dominating investor decision-making in non-cyclical consumer firms. This study contributes sector-specific empirical evidence under the post-reclassification market environment and provides practical insights for investors and corporate managers. Future research is encouraged to include additional variables or cross-sector comparisons.